A REVIVAL OF THE EXTINCT NAIL BLOCKS OF PADRA, VADODARA - Yadav, Rajni; Patel, Falguni; Lalwani, Yash (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Indian crafts are integral to the culture and customs of rural and tribal communities. Through the ages, crafts made in India have maintained their exclusiveness, but a lot of crafts are either extinct or on the verge of extinction due to non-diversification of product for the modern customer. One such example amongst many is the non-diversification in the motifs and colours of the Mud printing craft of Padra village. The main objective of the research was to revive indigenous nail blocks employed traditionally for mud resist printing. The blocks were revived by creating new motifs and layouts thus adding variation to prints, thereby expanding the motif vocabulary, popularizing mud resist printed fabric and reviving this dying craft tradition through traditional techniques with application of contemporary motif vocabulary and layout to open new areas of application for the craft in the global market. A case study approach was used and the information was collected from a purposely selected sample of the only surviving family of Padra, Vadodara even though they do not practice the craft, they still have the family heritage of knowledge about the craft. The researcher created new motifs and borders that were classified in two categories: Naturalistic and Geometric. Repeat layout patterns were designed using the selected motifs. Then these motifs, borders and repeat layout patterns were being evaluated through the preference schedule. The responses strongly indicated the need for intervention in this craft and that it can sustain if designs are accepted by the consumer. A consumer survey for the designed garments received good responses.